Analysis of Zakat Management Differences in Indonesia and Brunei Darussalam: Challenges and Solutions - Abdillah, Muhammad Hilmy; Nurwahidin; Hanase, Mulawarman; Subekti, Farih Wahyu (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This article analyzes the differences in zakat management in Indonesia and Brunei Darussalam, as well as the challenges faced and the solutions offered. Indonesia, with the largest Muslim population in the world, has a zakat system managed by the National Amil Zakat Agency (BAZNAS) and private zakat institutions. On the other hand, Brunei Darussalam, as a country that comprehensively implements Islamic law, manages zakat through centralized government institutions. The main differences lie in the organizational structure, collection mechanisms, distribution, and accountability of zakat. The main challenges in Indonesia include the lack of public awareness, transparency, and coordination among zakat institutions. In Brunei, the challenges are more focused on adjusting the zakat system to economic and social changes. This article offers solutions to address these challenges, such as increasing zakat literacy, strengthening information technology for transparency, and enhancing cooperation between the government and private institutions in Indonesia. For Brunei, the solutions include adjusting zakat policies to be responsive to economic dynamics and increasing public participation in the zakat system. This research is expected to provide insights for developing more effective zakat management in both countries, as well as contribute to global zakat literature